2020
DOI: 10.1186/s12885-020-6583-3
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the clinical use of PD-1/PD-L1 inhibitors: a questionnaire survey of oncologists in China

Abstract: Background: The purpose of the present study was to obtain information on the use of PD-1/PD-L1 inhibitors by oncologists in China through a national questionnaire survey. Methods: Between the 7th and 25th of July in 2019, a questionnaire designed by the Chinese Society of Clinical Oncology Immuno-Oncology (CSCO IO) Committee on the current status of the use of PD-1/PD-L1 inhibitors was distributed online and offline to cancer-related medical departments in thirty different provinces and autonomous regions of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 19 publications
(16 reference statements)
1
25
0
Order By: Relevance
“…Finally, immunotherapy with PD-1 or PD-L1 inhibitors has been approved for treating a variety of advanced human cancers, including lung squamous cell carcinoma, esophageal squamous carcinoma, cutaneous squamous cell carcinoma, and head and neck squamous cell carcinoma. 20 Here we also found that two patients had positive tumor PD-L1 expression, and one patient had positive PD-L1 expression on immune cells, indicating that PD-1/PD-L1 signaling pathway may be activated. Although immunotherapy has not been a clinical therapeutic approach for primary liver SCC, PD-1/PD-L1 blockade by PD-1 inhibitors may be developed as potential agents by activating the host’s anti-cancer immune response.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Finally, immunotherapy with PD-1 or PD-L1 inhibitors has been approved for treating a variety of advanced human cancers, including lung squamous cell carcinoma, esophageal squamous carcinoma, cutaneous squamous cell carcinoma, and head and neck squamous cell carcinoma. 20 Here we also found that two patients had positive tumor PD-L1 expression, and one patient had positive PD-L1 expression on immune cells, indicating that PD-1/PD-L1 signaling pathway may be activated. Although immunotherapy has not been a clinical therapeutic approach for primary liver SCC, PD-1/PD-L1 blockade by PD-1 inhibitors may be developed as potential agents by activating the host’s anti-cancer immune response.…”
Section: Discussionsupporting
confidence: 65%
“…In our cases, radiographic findings in major organs were negative and the tumors in the liver were diagnosed as primary. Primary SCC of the liver has been reported to be associated with hepatic cyst, chronic cholecystitis or hepatolithiasis in the majority of reported cases, 8,[11][12][13][14][15][16][17][18][19][20] and focal wall thickening of hepatic cysts or intrahepatic biliary from imaging might indicate a malignant change. However, its pathogenesis remains still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The PD-1/PD-L1 axis is of major interest as it is an immune checkpoint for T cells (24)(25)(26) as well as for NK cells (27)(28)(29). Originally described as an immune checkpoint for T lymphocytes, the inhibition of the PD-1/PD-L1 axis showed tremendous effects in clinical applications (30)(31)(32). In many malignant cancers, PD-L1 is upregulated to overcome the immune surveillance (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…The survey was developed according to our previous study ( Zhang et al, 2020 ). It was compiled after discussion and modification by the expert committees of the CSCO-IO and CSCO-PE.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, some preclinical studies have shown that the intestinal flora may significantly affect the efficacy of a therapy targeting PD-1/PD-L1 ( Sivan et al, 2015 ). Recently, we conducted a national questionnaire survey (which covered thirty different provinces and autonomous regions) to investigate the use of PD-1/PD-L1 inhibitors by oncologists in China ( Zhang et al, 2020 ) and found that increasing numbers of oncologists were interested in using PD-1/PD-L1 inhibitors. In this study, we further expanded our search by conducting a more extensive cross-sectional survey.…”
Section: Introductionmentioning
confidence: 99%